2019
DOI: 10.1371/journal.pone.0214004
|View full text |Cite
|
Sign up to set email alerts
|

Design of stable magnetic hybrid nanoparticles of Si-entrapped HRP

Abstract: Hybrid and composite nanoparticles represent an attractive material for enzyme integration due to possible synergic advantages of the structural builders in the properties of the nanobiocatalyst. In this study, we report the synthesis of a new stable hybrid nanobiocatalyst formed by biomimetic silica (Si) nanoparticles entrapping both Horseradish Peroxidase (HRP) (EC 1.11.1.7) and magnetic nanoparticles (MNPs). We have demonstrated that tailoring of the synthetic reagents and post immobilization treatments gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The difference was particularly significant when 100 nm MNPs (BioSi@β-Glc _Amine) were used instead of 200 nm MNPs (BioSi@β-Glc _PAA and BioSi@β-Glc_Doxi). Regardless of the impact that the size of the MNPs could have, the results correlate with those previously demonstrated by Correa et al [13] where the MNPs were found to have a profound effect on the silica matrix formation irrespective of the size of the aminated mediator of the Si synthesis. The values for polydispersity index of all the preparations vary around 0.3, indicating a homogeneous population of particles with a low probability of agglomeration.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The difference was particularly significant when 100 nm MNPs (BioSi@β-Glc _Amine) were used instead of 200 nm MNPs (BioSi@β-Glc _PAA and BioSi@β-Glc_Doxi). Regardless of the impact that the size of the MNPs could have, the results correlate with those previously demonstrated by Correa et al [13] where the MNPs were found to have a profound effect on the silica matrix formation irrespective of the size of the aminated mediator of the Si synthesis. The values for polydispersity index of all the preparations vary around 0.3, indicating a homogeneous population of particles with a low probability of agglomeration.…”
Section: Resultssupporting
confidence: 89%
“…The properties of immobilized biocatalysts on hybrid materials are partially determined by the individual effect of each material on the enzyme upon immobilization [13]. Therefore, as a first step in the integration of β-GIc in a material containing silica (Si) and MNPs, we studied the entrapment of the enzyme solely in biomimetic Si.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, León-Buitimea et al talked about the role of nanobioengineering in the development of smart therapeutics with programmed dynamic responses to target, release, and clear therapeutics in an efficient manner in the treatment of infectious diseases caused by virus and bacteria (León-Buitimea et al, 2020 ). Finally, Correa et al described the advances in her laboratory toward the design of hybrid composite nanoparticles that integrate enzymes to incorporate catalytic and superparamagnetic behaviors that would aid in designing drug delivery systems (Correa et al, 2019 ). The session was complemented with participants who exposed their research work on developing new drug delivery systems based on nanobioengineering to tackle different diseases, including tuberculosis, viral infections, including COVID-19, and cancer.…”
Section: Discussionmentioning
confidence: 99%